Dicopper(II) Complexes of the Antitumor Analogues Acylbis(salicylaldehyde hydrazones) and Crystal Structures of Monomeric [Cu2(1,3-propanedioyl bis(salicylaldehyde hydrazone))(H2O)2]·(ClO4) 2·3H2O and Polymeric {Cu2(1,6-hexanedioyl bis(salicylaldehyde hydrazone)) - Ranford, J.D. (2014)
Inorganic Chemistry